A synergy study of zinc borate in halloysite nanotube reinforced, siloxane epoxy base intumescent fire resistive coatings: Eine Synergieuntersuchung zu Zinkborat in, mit Halloysit-NanorÃ¶hren verstÃ¤rkten, Siloxane Epoxy basierten, intumeszenten feuerfesten Beschichtungen - Gillani, Q.F. (Wiley-VCH Verlag, 2018)
This study focuses the combined effects of halloysite nanotubes and zinc borate in siloxane epoxy base intumescent formulation when used with traditional intumescent ingredients e. g. ammonium polyphosphate, melamine and expandable graphite. Zinc borate was substituted in halloysite nanotube reinforced siloxane epoxy base intumesce fire retardant coatings and their effects on char morphology, char expansion, fire performance and thermal stability were characterized through field emission scanning electron microscopy, bunsen burner fire test and thermogravimetric analysis. During intumescent reaction, polydimethylsiloxane form char residue containing silica on the material surface and zinc borate, an inorganic flame retardant, releases boron oxide (B2O3) which effectively contribute to the char formation. Present study suggests that the existing synergism between polydimethylsiloxane and zinc borate is the result of chemical reaction via forming cross-linking BâOâSi structure. At the same time, alumina-siloxane film develops over the external layer of char due to release of alumina from halloysite nanotubes. Consequently, silicon, aluminum and boron elements together contribute to the integrity of char residue layer with better quality, achieving obviously improved flame retardancy compared to previous fire retardant systems. Â© 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim